Construção de uma des-ordem própria - Luís Francisco Cordeiro Pinto (2020)
The purpose of this master's thesis is to reflect on a own architectural-project. This study falls back on the intention to take consciousness of the complexity of the project, revealing which are the guiding principles, including its ontological dimension. Looking at architecture as a result of an association of circumstances and contingencies, the aim is to clarify the arguments and intentions underlying the dis-order of an architectural-project, bearing in mind its fragility, availability and susceptibility to change. Given the need and possibility to understand and identify the dynamics, consequences and purposes of the project process, the structure of the thesis is organised in four main moments: the first moment sets off from the analysis of the text "Design Materials" by Vittorio Gregotti, where the core of "project design" is clarified and the guiding materials of the procedure are reflected on; in a second moment, crossing over speeches, three masterarchitects are brought together: Álvaro Siza, Lina Bo Bardi, Peter Zumthor, key figures for the understanding of my project process; the third moment introduces three architectural projects: Leça Tides Swimming Pool, Sesc Pompeia of São Paulo and Thermal Baths of Vals, in an attempt to draw lessons and provocations from the different procedures; finally, the fourth moment enlightens the awakening circunstances of my architectural-project: a first year project exercise (2013), a fourth year project exercise (2017), the exchange experience in Buenos Aires and the subsequent visit to São Paulo (between 2017 and 2018). Alongside the main body of text, three interludes are developed with an analysis of the Leça Tides Pool project.